Effect of Clay Bricks Powder on the Fresh and Hardened Properties of Self-Compacting Concrete - ., Oday A. Abdulrazzaq (Iraqi Journal of Civil Engineering, 2018)
Fresh and hardened properties of self-compacting concrete was experimentally examined by replacing different percentages of cement by soft clay powder, which resulting from crushing the wastes of clay bricks. Three percentages (5%, 10%, and 15%) of cement were replaced with clay powder to study their effect on the properties of cement mortar and concrete of Grade (C35) in both fresh and hardened states. It was found that development rates of the compressive and tensile strengths for the mortar between ages of 7 to 28 days, decreased with increasing the percentage of the clay powder. Compared to the mix without clay powder, it was found that replacing (5%) from the cement causes a significant increase in the workability of the self-compacting concrete and the properties of the resulting hardened concrete such as compressive strength, tensile strength, and modulus of elasticity. While using (10%) and (15%) of the clay powder causes a significant decrease in the workability of the fresh concrete and the properties of the hardened concrete compared to mix without clay powder.